The Hidden Dangers of Plastic Use in the Food Industry: Implications for Diabetes and Public Health - Ashkar, Ihab; Masaabi, Maryam; Daas, Momena; Abdrabou, Eman; Karikm, Asima; Taha, Rama (Global Journal of Health Sciences, 2025)
Purpose: The high dependence on plastic in food processing and packaging introduces microplastics (MPs), nanoplastics (NPs), and endocrine-disrupting chemicals (EDCs) into the food chain, posing potential risks to public health, including immune alterations, inflammation, and metabolic disruptions linked to type 2 diabetes (T2DM). To assess the extent of plastic contamination in the food chain and its associated health effects, specifically focusing on the connection to T2DM. Methodology: A systematic literature search was conducted across PubMed, Google Scholar, and governmental health agency publications from the past five years, using keywords related to MPs, NPs, EDCs, T2DM, and plastic policy. Findings: MPs are widespread contaminants in the food chain, with major sources including marine organisms, bottled water, and packaging. Estimated annual human exposure ranges from 39,000 to 52,000 MP particles, with bottled water contributing up to 90,000 particles alone. MPs carry EDCs, such as bisphenols and phthalates, which are implicated in impaired insulin function and increased T2DM risk. Current filtration methods are insufficient to eliminate contamination, highlighting the need for stronger regulatory measures. While resources are spent on T2DM management, primary prevention remains inadequate. Unique Contribution to Theory, Practice and Policy: This study highlights the significant threat of plastics use- particularly MPs, NPs and EDCs within the foodcahin. It implements several key findings including: Public health risk, regulatory and policy reform, economic consideration as well as research prioritization. Overall, this study mitigates the health risks associated with plastic contamination, stricter regulations on plastic use in food processing and packaging are imperative, alongside incentives for biodegradable alternatives. Future research should prioritize investigating the long-term effects of MP exposure and developing innovative strategies to reduce plastic contamination in the food chain.